Disrupsi Decentralized Finance (DeFi) terhadap profesi akuntansi tradisional: Analisis kesiapan mahasiswa menghadapi transformasi pencatatan berbasis blockchain - Mubarok, Azmi sahlul (Maliki Interdisciplinary Journal, 2026)
The swift advancement of Decentralized Finance (DeFi) alongside blockchain technology poses a considerable challenge to the conventional accounting field. Systems that utilize distributed ledgers and smart contracts could potentially replace accountants as intermediaries and validators of transactions. This piece intends to assess how well-prepared accounting students are to navigate the shift from traditional bookkeeping to a decentralized financial landscape. By employing literature reviews and conceptual analysis techniques, the research examines students’ theoretical knowledge and their ability to adapt to the demands of blockchain technology. The findings reveal that although students recognize the potential risk of technological upheaval, their comprehension of smart contract auditing and DeFi governance is still quite limited. This change necessitates a transformation in the role of accountants, requiring them to evolve from basic record-keepers to strategic analysts and auditors of blockchain systems. Consequently, this study emphasizes the pressing need for higher education institutions to update accounting programs to include contemporary financial technology education. Such modifications are essential to develop graduates who are versatile and in alignment with the needs of the industry.